The use of fibrinolysis inhibitors in cardiac surgery with cardiopulmonary bypass (literature review) - V. Yu. Medvedeva; K. N. Khrapov; A. A. Khryapa; K. Yu. Kankova (Вестник анестезиологии и реаниматологии, 2024)
In cardiac surgery with cardiopulmonary bypass (CPB) is a common complication. The incidence of this complication in cardiac surgery patients is estimated at about 10%. For this reason, the introduction of a patient blood management (PBM) in cardiac surgery is extremely relevant. Antifibrinolytic therapy is a key pharmacological tool of a multimodal PBM in cardiac surgery with CPB. The use of antifibrinolytics (tranexamic acid (TXA) and epsilon aminocaproic acid (EACA)) is standard practice in complex cardiac surgery with CPB. However, there is currently ongoing discussion regarding the search for the optimal dose of EACA and TXA to achieve an effective concentration in blood plasma in order to inhibit fibrinolysis with the minimization of adverse events. The use of aprotinin has a number of potential advantages, but its use in routine clinical practice is significantly limited. This review presents modern approaches to antifibrinolytic therapy, examines the mechanisms of action of the main drugs, highlights the side effects associated with the use of antifibrinolytic agents.